Statistical modeling for biomedical researchers a simple introduction to the analysis of complex data - Dupont, William D. (William Dudley), 1946- (Cambridge : Cambridge University Press, 2002)
This text will enable biomedical researchers to use several advanced statistical methods that have proven valuable in medical research. The emphasis is on understanding the assumptions underlying each method, using exploratory techniques to determine the most appropriate method, and presenting results in a way that will be readily understood.
Ch. 1. Introduction -- Ch. 2. Simple linear regression -- Ch. 3. Multiple linear regression -- Ch. 4. Simple logistic regression -- Ch. 5. Multiple logistic regression -- Ch. 6. Introduction to survival analysis -- Ch. 7. Hazard regression analysis -- Ch. 8. Introduction to poisson regression: inferences on morbidity and mortality rates -- Ch. 9. Multiple poisson regression -- Ch. 10. Fixed effects analysis of variance -- Ch. 11. Repeated-measures analysis of variance.
Includes bibliographical references and index.
Print version record.
Keywords: Medicine -- Research -- Methodology; Medicine -- Research -- Mathematical models; Medicine -- Research -- Statistical methods; Biometry; Models, Statistical; Data Interpretation, Statistical; Mathematical Computing; MEDICAL -- Biostatistics; Medicine -- Research -- Mathematical models; Medicine -- Research -- Methodology; Medicine -- Research -- Statistical methods; Andre fag (naturvidenskab og teknik) -- Andre fag; Problems and Exercises; Electronic books